Fermentation of sugarcane juice and molasses for ethanol production - Laluce, Cecília [UNESP]; Leite, Guilherme R. [UNESP]; Zavitoski, Bruna Z. [UNESP]; Zamai, Thamires T. [UNESP]; Ventura, Ricardo (Wiley, 2016)
The quality of both sugarcane juice and molasses is affected by the nutrients and topology of the soil, variety of sugarcane, climate and harvesting. This chapter describes the natural microbial ecology of the ethanol production process, methods for yeast identification, bioreactors and fermentation processes, cleaning and sanitization, and process control for industrial ethanol production from sugarcane juice and molasses. The main steps in the production of anhydrous bioethanol from sugarcane are as follows: reception and cleaning of the sugarcane, extraction of sugars, juice heating, clarification treatments, concentration, fermentation, distillation, and dehydration. Recently, multistage-based fermentation systems have been designed for the propagation of yeast cells, using supplemented molasses due to increasing demand for starter yeast by food and bioethanol industries. Sugarcane juice, syrups, and molasses resulting from the sugarcane processing in sugar mills are used in fermentations.
Keywords: Bioethanol; Bioreactor; Ethanol production; Fermentation; Microbial ecology; Molasses; Sugarcane juice